Epimorphin alters the inhibitory effects of SOX9 on Mmp13 in activated hepatic stellate cells. - James Pritchett; Varinder S Athwal; Emma Harvey; Katherine Martin; Jessica Llewellyn; Philip Ireland; Alexander Nicolaides; Martin J Humphries; Nicoletta Bobola; Neil A Hanley; Karen Piper Hanley (PLoS ONE)
Background and aims Liver fibrosis is a major cause of morbidity and mortality. It is characterised by excessive extracellular matrix (ECM) deposition from activated hepatic stellate cells (HSCs). Although potentially reversible, treatment remains limited. Understanding how ECM influences the pathogenesis of the disease may provide insight into novel therapeutic targets for the disease. The extracellular protein Epimorphin (EPIM) has been implicated in tissue repair mechanisms in several tissues, partially, through its ability to manipulate proteases. In this study, we have identified that EPIM modulates the ECM environment produced by activated hepatic stellate cells (HSCs), in part, through down-regulation of pro-fibrotic Sex-determining region Y-box 9 (SOX9). Methods Influence of EPIM on ECM was investigated in cultured primary rat HSCs. Activated HSCs were treated with recombinant EPIM or SOX9 siRNA. Core fibrotic factors were evaluated by immunoblotting, qPCR and chromatin immunoprecipitation (ChIP). Results During HSC activation EPIM became significantly decreased in contrast to pro-fibrotic markers SOX9, Collagen type 1 (COL1), and α-Smooth muscle actin (α-SMA). Treatment of activated HSCs with recombinant EPIM caused a reduction in α-SMA, SOX9, COL1 and Osteopontin (OPN), while increasing expression of the collagenase matrix metalloproteinase 13 (MMP13). Sox9 abrogation in activated HSCs increased EPIM and MMP13 expression. Conclusion These data provide evidence for EPIM and SOX9 functioning by mutual negative feedback to regulate attributes of the quiescent or activated state of HSCs. Further understanding of EPIM's role may lead to opportunities to modulate SOX9 as a therapeutic avenue for liver fibrosis.